Anatomical markers and Phytochemical study of different plant parts of Bacopa monnieri (L.) Wettst. - Varshney Anju; Chandra Naresh; Patil Avinash (International Journal of Life Sciences, 2017)
Bacopa monnieri (L.) Wettst. (Scrophulariaceae) commonly known as “brahmi”, has been used in the traditional systems of medicines as "Medhya Rasayana" as it increases mental clarity and brain stimulating action. It is also being used as anti-inflammatory, analgesic, antipyretic, sedative, antioxidant and anti-cancerous agent. The present study was carried out to provide characteristic anatomical markers for root, stem and leaf, along with this study preliminary photochemical analysis was also carried out for the presence of major secondary metabolites which can act as the indicator of bioactivity of the different plant parts of Bacopa monnieri (L.) Wettst. The distinguishing features for root and stem are simple starch grains, xylem vessel with spiral thickenings, pitted tracheids and for leaf are sub- epidermal foliar idioblast, sessile, multicellular trichome and prismatic calcium oxalate crystals. Presence of two types of stomata i.e. anomocytic and diacyitc in the same field of vision under 45X magnification, are seen in the surface preparation as well as in the powder microscopy of Bacopa monnieri leaf. This is the major observation of the study. All these distinguishing features can be used as anatomical markers for correct indentification of root, stem and leaf of the plant. Preliminary phytochemical analysis revealed the presence of alkaloids, saponins, flavonoids, tannins, carbohydrates, proteins and anthroquinones in different plant parts of Bacopa monnieri while quantitative estimation showed that alkaloids (mg /g dry weight) in root, stem and leaf were found to be 1.67 ± 0.577, 47.00 ± 0.81 and 53.07 ± 2.08 respectively; saponins (mg /g dry weight) in root, stem and leaf were 7.50 ± 0.71, 23.33 ± 1.53 and 57.00 ± 2.65 respectively and flavonoids (mg /g dry weight) in stem and leaf were 25.33 ± 1.53 and 27.67 ± 2.08 respectively. Thus the findings of the present study will provide referential pharmaco - botanical information for correct identification and authentication of the crude drug and its plant parts.